The Influence of Danu Suci Gus Teja's Instrumental Music on Hypertension in the Elderly in Pucaksari Village | Pengaruh Musik Instrumental Danu Suci Gus Teja Terhadap Hipertensi Pada Lansia Di Desa Pucaksari - Ni Made Intan Dwani Anantara; I Wayan Artana; Si Putu Agung Ayu Pertiwi Dewi (GHURNITA: Jurnal Seni Karawitan, 2023)
Hypertension can have bad effects if handled improperly. These impacts include stroke, heart disease, epilepsy, and glaucoma, so this disease needs proper treatment. Hypertension treatment can be done with pharmacological and non-pharmacological treatment. One of the non-pharmacological treatments is listening to instrumental music. This study aimed to determine Gus Teja's Danu Suci instrumental music influence on hypertension in the elderly in Pucaksari Village, Busungbiu, Buleleng. This study used the experimental method with Pretest-Posttest with 40 elderlies as a sample and was selected by purposive sampling. The data collection method used an observation sheet, and the blood pressure measurement device used a digital Sphygmomanometer, then analyzed using the Wilcoxon statistical test. The study's results showed that the average systolic blood pressure before and after listening to instrumental music was 11.78, while the average difference in diastolic blood pressure was 7.75. Gus Teja's Danu Suci instrumental music can significantly reduce systolic blood pressure in older adults in Pucaksari Village (p-value <0.05) and diastolic with a p-value <0.05. Older adults in Pucaksari Village should listen to Gus Teja's Danu Suci instrumental music to reduce their systolic and diastolic blood pressure apart from using the medicine.